Impacto socioeconómico de la Unidad Educativa del Milenio “Temístocles Chica Saldarreaga” en el sitio San Pablo de Tarugo Canuto-Chone - Calderón Ganchozo, Vanessa Alexandra (2019)
The present investigative work consisted in determining the socio-economic impact and administrative management of the Educational Unit of the Millennium "Temístocles Chica Saldarreaga" in the San Pablo de Tarugo Canuto-Chone site, to achieve this objective research methods such as induction, deductive, analysis-synthesis and Delphi, the same ones that detail characteristics or features of the phenomenon of the object of study, as well as techniques; such as the interview, survey, work with experts and the statistical technique, relevant information was collected about the institution, characterizing the infrastructure, the teachers that comprise it, students who have graduated in the period 2011-2017, and their socioeconomic environment of the San Pablo de Tarugo Canuto-Chone site. A system of indicators was established to measure the socioeconomic impact of the Millennium Education Unit, based on the bibliographic analysis and Delphi method, obtaining a total of two social indicators, an economic indicator and three management indicators. The measurement of socioeconomic and administrative management impacts, based on the system of established indicators that was determined to social indicators respectively, there is a positive impact that benefits the population of the San Pablo de Tarugo site, with the implementation of the Millennium Education Unit. The economic indicator made it possible to evaluate those graduate students in the respective periods, evidencing a negative impact, with low standards of probability in the labor field, and the indicators of administrative management, allowed to demonstrate a positive impact, evaluating the body of teachers and administrators with excellent satisfaction results, the number of graduates indicates a growing trend and the infrastructure of the Millennium Education Unit could not be measured because there was no comparison information with the previous administration.